AMEE Guide to ethical teaching in online medical education: AMEE Guide No. 146. (2nd November 2022) - Masters, Ken; Taylor, David; Loda, Teresa; Herrmann-Werner, Anne
Abstract: The Covid-19 pandemic necessitated Emergency Remote Teaching (ERT): the sudden move of educational materials online. While ERT served its purpose, medical teachers are now faced with the long-term and complex demands of formal online teaching. One of these demands is ethical online teaching. Although ethical teaching is practiced in face-to-face situations, online teaching has new ethical issues that must be accommodated, and medical teachers who wish to teach online must be aware of these and need to teach ethically. This Guide leads the medical teacher through this maze of complex ethical issues to transform ERT into ethical online teaching. It begins by setting the context and needs and identifies the relevant fundamental ethical principles and issues. It then guides the medical teacher through the practical application of these ethical principles, covering course design and layout (including the curriculum document, implementation, on-screen layouts, material accessibility), methods of interaction (synchronous and asynchronous), feedback, supervision and counselling, deeper accessibility issues, issues specific to clinical teaching, and assessment. It then discusses course reviews (peer-review and student evaluations), student monitoring and analytics, and archiving. The Guide aims to be a useful tool for medical teachers to solidly ground their online teaching practices in ethical principles.